“Saving the Euro: A Test for Globalisation” (The Allama Iqbal Lecture) (The Pakistan Development Review, 2012)
The sovereign debt crisis originating in the eurozone immediately after the eruption of the global financial crash represents a significant challenge not only for the European but also for the world economy. Overcoming it will contribute to creating the conditions for sustained global economic recovery and also provide a testing ground for our capabilities to control the dangers surrounding the globalisation process which is unfolding over the recent decades. The integration of markets in products and finance, and less so in services, coupled with enormous technological progress in communications and transport diffused growth to regions and continents that, during the last centuries, had been left behind the dramatic rise in living standards witnessed in Europe, North America and Japan since the Industrial Revolution. The opening up of markets led to more efficient use of global resources allowing productivity to grow while billions of people transgressed poverty lines and joined the modern world. The downside of this process is that national control over economic policy has been significantly diminished, even vanished for small economies, while intricate problems emerged for international economic governance. These problems were brought to the fore during the recent crisis at the global and eurozone level. As markets integrate and systems converge, controlling imbalances in either the real economy or the financial sector becomes increasingly difficult since it requires much more advanced policy cooperation than allowed for in institutional set-ups corresponding to nation-centred economic models. The extent of the changes that are needed will become clearer as we review the origins of the present crisis. At the global level the huge current account imbalances that have been built up over the last decades produced an unusual pattern of savings flows. Poor countries, chiefly China, have been financing rich ones, such as the United States. This pattern reflects the fact that emerging countries have had large current account surpluses, whereas developed economies have accumulated sizeable deficits. The imbalances led capital to flow ‘the wrong way’ from the developing to the advanced economies, destabilising the financial system and thus creating the conditions for the economic crisis.